Менаџмент на човечки ресурси во непрофитни организации (НПО) – состојби и перспективи - Маџовски, Јован (Економски факултет, УКИМ, Скопје, 2014)
Human Resources are very specific in the nonprofit organizations (NPOs). Small NPOs as well as small companies are not focused on the management of the human resources but as they grow this organizational function imposes itself. In both profit and nonprofit organizations results and success are based on people. This is even more obvious with the nonprofit organizations as it is very rare that one NPO becomes more successful than the others because of usage of new technology, newer equipment, larger production facilities, economy of scale, cheaper financial sources, etc. In the nonprofit world people, i.e. employees, volunteers and management are the only reasons for growth and success. This doctorial thesis defines nonprofit organizations, elaborates on the forms and types of NPOs, points the differences and similarities between profit and nonprofit sectors in the area of Performance Management System and analyses the specifics of the human resources management in the nonprofit organizations such as volunteers and Executive Board. The last part of this doctorial thesis makes comparative analyses of the nonprofit and profit human resource management practices in Macedonia and globally in order to propose human resource management recommendations for the nonprofit organizations based on their size and life cycle stage of growth. This research study concludes that one of the secrets for the success of the nonprofit organizations lies exactly in the human resource management - building teams, engaging and managing committed employees, managers and volunteers, building cohesive and engaged Executive Board and setting the right organizational structure to fulfill the mission versus earning profit.
Management of human resources in non profit organizations – current conditions and perspectives
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: human resource management, nonprofit organizations, performance management system, Macedonia